1981
DOI: 10.1172/jci110308
|View full text |Cite
|
Sign up to set email alerts
|

Renal inner medullary prostaglandin synthesis. A calcium-calmodulin-dependent process suppressed by urea.

Abstract: A B S T R A C T Previous studies have dlemonstrated that hyperosmolar NaCl and miiannitol stimulate immunoreactive prostaglandin E (iPGE) production by slices of inner medulla (IM), wherease urea inhibits this process. In the present study, the roles of Ca21 and calmodulin in the control of PCE synthesis in IM and the basis for the differential actions of solutes were examined. A23187 increased ['4C]arachidonate (AA) release and iPGE accumulatioin in the presence but not in the absence of media Ca2+ whereas s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…iPGE content was assessed as previously reported (2,14,15 Extraction and assay of DNA. DNA content of the colonic mucosa was extracted as previously described (6).…”
Section: Methodsmentioning
confidence: 99%
“…iPGE content was assessed as previously reported (2,14,15 Extraction and assay of DNA. DNA content of the colonic mucosa was extracted as previously described (6).…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, recent studies have shown that calcium enhances prostaglandin synthesis. 33 " 35 The purposes of the present study therefore were 1) to determine the cardiovascular mechanisms of the pressor response to acute hypercalcemia in the conscious rat and 2) to evaluate a possible enhancing and vasoconstrictive role for angiotensin II, catecholamines, and vasopressin; a possible attenuating and vasodilative role for prostaglandins and parathyroid hormone; and the role of cellular calcium uptake in the pressor response.…”
mentioning
confidence: 99%
“…Alternatively, calcium ion could directly, independent of AII, mediate the decrement in RBF and GFR in chronic hypercalcemia (19). On the other hand, the vasodilatory renal prostaglandins (PG), whose synthesis in vitro has been shown to be stimulated by calcium ion (20)(21)(22), could have an attenuating effect on the vasoconstrictor activity of AII and calcium ion. The present experiments were therefore performed to (a) assess the systemic and renal hemodynamic effect of chronic hypercalcemia in the conscious rat, and (b) determine the role of PG, AII, and calcium per se in the control of RBF and GFR in such a setting.…”
mentioning
confidence: 99%